Analysis Influence Working Capital Investment On Company Value and Investment Decisions Long Term : An Empirical Study of the Sector Manufacturing 2014 – 2023 in Indonesia - Khaesarani, Rena; Rokhim, Rofikoh (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This research aims to investigate the impact of working capital investment on firm value and long-term investment decisions in the manufacturing sector in Indonesia. The study utilizes annual panel data from 100 to 150 manufacturing firms listed on the Indonesia Stock Exchange (IDX) during the period 2014-2023. Findings indicate that efficient working capital investment has a positive influence on firm value and long-term investment decisions. This study utilizes the Trade-Off, Agency, and Resource-Based View theories as a framework. The results provide valuable implications for finance managers in the manufacturing sector to optimize working capital management to enhance firm profitability and long-term growth.